FoxO6 affects Plxna4-mediated neuronal migration during mouse cortical development - Paap, Ricardo H. (Proc Natl Acad Sci U S A, 2016)
The forkhead transcription factor FoxO6 is prominently expressed during development of the murine neocortex. However, its function in cortical development is as yet unknown. We now demonstrate that cortical development is altered in FoxO6(+/−) and FoxO6(−/−) mice, showing migrating neurons halted in the intermediate zone. Using a FoxO6-directed siRNA approach, we substantiate the requirement of FoxO6 for a correct radial migration in the developing neocortex. Subsequent genome-wide transcriptome analysis reveals altered expression of genes involved in cell adhesion, axon guidance, and gliogenesis upon silencing of FoxO6. We then show that FoxO6 binds to DAF-16–binding elements in the Plexin A4 (Plxna4) promoter region and affects Plxna4 expression. Finally, ectopic Plxna4 expression restores radial migration in FoxO6(+/−) and siRNA-mediated knockdown models. In conclusion, the presented data provide insights into the molecular mechanisms whereby transcriptional programs drive cortical development.